Lateral Bilayer MoS2–WS2 Heterostructure Photodetectors with High Responsivity and Detectivity. Issue 20 (26th July 2019) - Ye, Kun; Liu, Lixuan; Liu, Yujie; Nie, Anmin; Zhai, Kun; Xiang, Jianyong; Wang, Bochong; Wen, Fusheng; Mu, Congpu; Zhao, Zhisheng; Gong, Yongji; Liu, Zhongyuan; et al.
Abstract: 2D heterostructures combining different layered semiconductors have received great interest due to their intriguing electrical and optical properties. However, the arbitrary growth of layers in a lateral heterostructure remains a challenge. Here, the synthesis of large‐scale lateral bilayer (LBL) WS2 –MoS2 heterostructures is reported by a two‐step chemical vapor deposition route. Raman, photoluminescence, and second‐harmonic generation images show the sharp boundaries between WS2 and MoS2 domains in the heterostructure. Atomically resolved scanning transmission electron microscopy further reveals that sharp boundaries are formed by seamless connections via a lateral zigzag epitaxy between WS2 and MoS2 . Notably, the photodetector device based on the LBL WS2 –MoS2 heterostructure exhibits ultrahigh photoresponsivity and detectivity (6.72 × 10 3 A W −1 and 3.09 × 10 13 Jones for 457 nm laser light, respectively), orders of magnitude higher than those of MoS2 and WS2 monocrystals. These excellent performances render LBL WS2 –MoS2 heterostructures as promising candidates for next‐generation optoelectronics. Abstract : Lateral bilayer (LBL) WS2 –MoS2 heterostructures have been successfully synthesized via a two‐step CVD growth method. The photodetector device, based on the LBL WS2 ‐MoS2 heterostructure, exhibits ultrahigh photoresponsivity and detectivity (6.72 × 10 3 A W ‐1 and 3.09 × 10 13 Jones for 457 nm laser light), orders of magnitude higher than those of MoS2 and WS2 monocrystals.